Shape Understanding System Knowledge Implementation and Learning - Les, Zbigniew. (Studies in Computational Intelligence, 2013)
This book presents the selected results of research on the further development of the shape understanding system (SUS) described in our previous book titled Shape Understanding System: the First Steps Toward the Visual Thinking Machines . This is the second book that presents the results of research in the area of thinking and understanding carried out by authors in the newly founded the Queen Jadwiga Research Institute of Understanding. In this book, the new term knowledge implementation is introduced to denote the new method of the meaningful learning in the context of machine understanding. SUS ability to understand is related to the different categories of objects such as the category of visual objects, the category of sensory objects and the category of text objects. In this book, new terms and concepts are introduced in order to describe and explain some issues connected with SUS development. These terms are explained by referring to the content of our books and other our works rather than to existing literature in related areas of research. This book raises many questions that are discussed in the area of cognitive science or philosophy of mind.